Autoimmune Haemolytic Anaemia Following Influenza A Pandemic H1N1 Infection: A Case Report - Bandyopadhyay, Pritam; Biswas, Tamoghna; Lahiri, Mahuya (Journal of Nepal Paediatric Society, 2019)
Autoimmune haemolytic anaemia has been rarely reported in association with influenza virus. Here, we report a 16 months old girl with warm autoimmune haemolytic anaemia following influenza A Pandemic H1N1 infection, which improved with oral corticosteroids and intravenous immunoglobulin.